2016
DOI: 10.1177/0962280215623981
|View full text |Cite
|
Sign up to set email alerts
|

Identification of predicted individual treatment effects in randomized clinical trials

Abstract: In most medical research, treatment effectiveness is assessed using the Average Treatment Effect (ATE) or some version of subgroup analysis. The practice of individualized or precision medicine, however, requires new approaches that predict how an individual will respond to treatment, rather than relying on aggregate measures of effect. In this study, we present a conceptual framework for estimating individual treatment effects, referred to as Predicted Individual Treatment Effects (PITE). We first apply the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 68 publications
(127 reference statements)
0
56
0
Order By: Relevance
“…An overview of several methods for obtaining the predicted individual treatment effect (PITE), including machine learning algorithms and non-parametric models such as tree-based methods is provided by Lamont et.al. [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…An overview of several methods for obtaining the predicted individual treatment effect (PITE), including machine learning algorithms and non-parametric models such as tree-based methods is provided by Lamont et.al. [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In sum, we have shown that, while conventional approaches to effect size estimation in policy interventions often resort to aggregated measures of impact, such as ATE or conditional ATE 35,40 , these evaluations take little note of individual characteristics that may alter individual responses to interventions. After all, an intervention that worked well on average may not be the best option for all 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment recommendations can be based on ATE when response-modifying patient characteristics are absent. 33 …”
Section: State-of-the-art For Developing Prediction-based Recommendatmentioning
confidence: 99%
“…This may not apply if the clinical response is modulated by other (observable) variables Z (called effect modifiers) and if the individual patient deviates significantly from the average through his set of modifiers. 33 A simple example is the different response to prasugrel across several subgroups, which can be attributed to effect modifiers (eg, age, weight, and medical history). More complex cases are often not well described, also because they neither have been identified nor comprehensively evaluated nor adequately reported.…”
Section: State-of-the-art For Developing Prediction-based Recommendatmentioning
confidence: 99%